Digital Giza : Visualizing the Pyramids - Der Manuelian, Peter, (MetaLAB Projects., 2017)
"After a brief introduction to the Giza Plateau of the Old Kingdom and a summary of the history of excavation at the site, this book explores new, primarily digital, approaches to accessing the site. A 3-D reconstruction of the site allows for both general access and targeted research inquiries that were previously impossible, even at the site itself. Case studies and philosophical musings on the nature of visualization in archaeology round out the volume, along with some speculation about emerging technologies and possible next steps."--